Dávný český pokus o sociologii zvířat: Zdeněk Ullrich: Společnosti ve světě zvířat (1928) - Ullrich, Zdeněk; Komárek, Stanislav (Lidé města, 2019)
An edition of the little-known text by Zdeněk Ullrich (1901–1955), one of the founding figures of Czech sociology and a significant representative of the interwar Prague School of Sociology. Within the extensive scope of the introduction to this discipline, of which, luckily, only this one part was published, the author postulated a sort of animal sociology that transcends any studies in ethology and moves towards a generously conceived general anthropology, the so-called human-animal studies. The sociologically interpreted biological findings were probably to serve as a basis for Ullrich’s own understanding of sociology, which, however, the author came to define only much later and under different circumstances (lectures at the Univerity of Politics and Social Issues immediately following World War II). Although this text remained a torso, it gives interesting witness to the intellectual richness of Czech social sciences in the interwar period.